Chewing lice of Procellaria aequinoctialis Linnaeus, 1758 in Brazil with a new host record. (April 2023) - Brener, Beatriz; Lira, Sarah; Antonello, Magda
Abstract: The white-chinned petrel ( Procellaria aequinoctialis ) is a seabird widely distributed in the circumpolar sub-Antarctic islands and subtropical regions, including Brazilian waters. Among the parasites present on the white-chinned petrel are the chewing lice. This seabird is parasitized by 4 known lice species to date. In this study we evaluated the ectoparasites of 2 white-chinned petrels rescued by an animal rehabilitation center in Rio de Janeiro, Brazil and recorded 4 species of chewing lice, of which 3 are already known for this host. One of the species however, has never been recorded in Brazil and another one has never been recorded parasitizing P. aequinoctialis, making this a new host record. Highlights: Animal Reabilitation Center analyzes White-chinned-petrel for ectoparasites. New louse-host association in Procellaria aequinoctialis from Brazil. First record of Austromenopon popellus in White-Chinned-Petrel in Brazil. Austromenopon echinatum new host, the white-chinned-petrel.